KEPUTUSAN KONSUMEN DALAM PEMBELIAN TIKET DI PT. RIAU KARSA PELITA KOTA PEKANBARU - Helna Manda Hayati; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purposed of this research to know what are the factors of consumer decision in buying tickets in the PT. Riau Karsa Pelita Pekanbaru and also to know what is the main factor in buying the tickets by consumer PT. Riau Karsa Pelita Pekanbaru.This research used descriptive qualitative method for analyzed the problem. The sample in this research are 100 samples by using accidental sampling. And then the technique for collected the data in this research are using observation, questionnaire and interview. And it is using skala likert to know the the length of intervals.Based on the research, there are four factors consumer in buying it is the factor of the price, product (service), promotion and location. The consumer was agree with the factor the price, location and promotion as a decided factor buying and then the consumer also was really agree the product factor as the main factor in buying tikets in the PT. Riau Karsa Pelita.Key words: consumer decision, price, product, promotion, location